Lightweight high-frequency wave-transparent composite material with low dielectric property and preparation method of lightweight high-frequency wave-transparent composite material
By adding high-performance hollow glass microspheres to the low-polar epoxy resin composition, a lightweight high-frequency wave-transmitting composite material with low density, low dielectric and high strength is prepared, and the medium and high-frequency dielectrics of the prior art are solved. The problem of large losses achieves efficient high-frequency signal transmittance.
Patent Information
- Application Number
- CN202411693330.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
AI Technical Summary
The existing epoxy glass fiber composite materials have a large dielectric loss at high frequencies, which is difficult to meet the signal transmittance requirements of 5G communication.
By adding high-performance hollow glass microspheres to the low-polar epoxy resin composition, a lightweight high-frequency wave-transmitting composite material with low density, low dielectric, and high strength is prepared. The method includes mixing epoxy resin, curing agent, accelerator and hollow glass microspheres, immersing them in a fiberglass cloth, baking and hot pressing to form the target product.
It achieves a dielectric loss below 0.01 at 5GHz, improves high-frequency signal transmittance, and meets the demand for consumer electronics housing and peripheral products of 5G communication.
Smart Images

Figure CN119505480A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and more specifically, to a lightweight high-frequency wave-transmitting composite material with low dielectric properties and a preparation method thereof. Background Art
[0002] Due to its higher strength than plastic, lower weight than glass and higher toughness, epoxy fiberglass board is increasingly widely used as a reinforcing material for the outer shells of consumer electronic products such as mobile phones and tablet computers or consumer electronic peripherals such as leather cases and keyboards.
[0003] With the popularization of 5G communications, 5G consumer electronic products have higher and higher requirements for the signal transmittance of casing materials. Since ordinary epoxy resins have relatively large dielectric constants and dielectric losses at high frequencies, their transmittance to 5G high-frequency electromagnetic signals is increasingly difficult to meet the requirements of 5G communications.
[0004] Hollow glass microspheres are hollow, thin-walled, hard, lightweight spheres with excellent properties such as low density, high strength, sound insulation, heat insulation, and stable chemical properties. The Chinese document with publication number CN109825033A prepares epoxy glass fiber copper clad laminate materials with lower density and lower dielectric constant by adding hollow glass microspheres, but its dielectric loss is relatively large, which is not conducive to the penetration of 5G high-frequency signals. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a lightweight high-frequency wave-transmitting composite material with low dielectric properties and a preparation method thereof, which has the advantages of low density, high strength and low dielectric loss.
[0006] The above technical objectives of the present invention are achieved through the following technical solutions: a method for preparing a lightweight high-frequency wave-transmitting composite material with low dielectric properties, comprising the following steps:
[0007] S1. Add epoxy resin, curing agent and accelerator to the solvent, stir and evenly dissolve, then add hollow glass microspheres, stir and evenly disperse to obtain resin glue;
[0008] S2, immersing the glass fiber cloth into the resin glue solution, taking it out after it is completely soaked, and baking it to obtain a prepreg;
[0009] S3, stacking, hot pressing, and cooling a plurality of the prepregs to obtain a target product;
[0010] Among them, the curing agent includes one or more of active ester, styrene maleic anhydride resin, benzoxazine resin and bismaleimide resin, and the epoxy resin includes one or more of bisphenol A type epoxy resin, isocyanate modified epoxy resin, dicyclopentadiene modified epoxy resin and biphenyl type epoxy resin.
[0011] In one embodiment, the mass fractions of each component in the resin glue are:
[0012] Epoxy resin 80-120 parts;
[0013] Curing agent 20-100 parts;
[0014] Accelerator 0.05-0.5 parts;
[0015] Hollow glass microspheres 20-80 parts.
[0016] In one embodiment, the accelerator includes one or more of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, N,N-dimethylaminopyridine and 2,4,6-tris(dimethylaminomethyl)phenol.
[0017] In one embodiment, the solvent includes one or more of acetone, butanone, xylene, propylene glycol methyl ether, ethylene glycol monomethyl ether and cyclohexanone.
[0018] In one embodiment, the hollow glass microspheres are high-performance borosilicate hollow glass microspheres, and the density of the high-performance borosilicate hollow glass microspheres is 0.2-0.6 g / cm 3 , particle size D50 is 30-75μm, and particle size D90 is 60-120μm.
[0019] In one embodiment, the step S1 further includes adding an auxiliary agent, wherein the auxiliary agent includes one or more of a pigment, a cross-linking auxiliary agent, an initiator, an antioxidant and a UV absorber.
[0020] In one of the embodiments, in S3, an interlayer is stacked between two adjacent prepregs, and the interlayer includes one of a plate, a metal sheet, a magnet, a prepreg and a fiber cloth.
[0021] In one embodiment, the specific steps of hot pressing in S3 are:
[0022] The composite layer is hot pressed in a stepwise manner with a temperature of 120-220°C and a pressure of 5-25 kg / cm 2 ;
[0023] Then, the composite layer is heat-pressed at 170-190° C. for 30-120 minutes.
[0024] A light-weight high-frequency wave-transmitting composite material with low dielectric properties is prepared by the preparation method of the light-weight high-frequency wave-transmitting composite material with low dielectric properties.
[0025] The above-mentioned lightweight high-frequency wave-transmitting composite material with low dielectric properties and its preparation method have the following beneficial effects:
[0026] The present invention adds high-performance hollow glass microspheres to a low-polarity epoxy resin composition, so that the obtained composite material has the characteristics of low density, low dielectric and high strength. Compared with the traditional epoxy glass fiber composite material filled with hollow glass microspheres, it has lower dielectric loss and the dielectric loss at 5GHz is less than 0.01, so it has higher high-frequency signal transmittance, which fully meets the demand for consumer electronic product casings and peripheral products in the 5G communication era. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a flow chart of the steps of the present invention;
[0028] Figure 2 This is a comparison diagram of the reaction mechanisms of epoxy resin cured by different curing agents in the present invention. DETAILED DESCRIPTION
[0029] The present invention is described in further detail below in conjunction with the embodiments. It should be noted that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on it. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definitions in this specification shall prevail.
[0030] As used herein, the term "prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0031] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0032] When amount, concentration or other value or parameter is expressed as range, preferred range or a series of upper preferred value and lower preferred value limit range, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.
[0033] A method for preparing a lightweight high-frequency wave-transmitting composite material with low dielectric properties, such as Figure 1 As shown, the following steps are included:
[0034] S1. Add epoxy resin, curing agent and accelerator to the solvent, stir and evenly dissolve, then add hollow glass microspheres, stir and evenly disperse to obtain resin glue;
[0035] In actual production, epoxy resin, low-polarity curing agent, and accelerator are first gradually added to the solvent to dissolve to form a homogeneous solution, and then the hollow glass microspheres are gradually added to the homogeneous solution in batches and stirred at a medium speed to disperse them evenly; the low-polarity curing agent used makes the obtained resin glue have the characteristics of low dielectric loss.
[0036] S2, immersing the glass fiber cloth into the resin glue solution, taking it out after it is completely soaked, and baking it to obtain a semi-cured sheet;
[0037] In actual production, the glass fiber cloth is electronic grade glass fiber cloth, and electronic grade glass fiber cloth with different basis weights is selected according to actual needs. The commonly used basis weight is 48g / m 2 1080 glass fiber cloth, basis weight is 78g / m 2 2113 glass fiber cloth, basis weight is 105g / m 2 2116 glass fiber cloth, etc.; in addition, the baking temperature in S2 is 150-210°C, preferably 170-190°C, and the baking time is 2-10 minutes, preferably 3-6 minutes. The process parameters of gluing are determined by the gelation time of the glue, the physical properties of the semi-cured sheet to be prepared, the gluing equipment used, etc.
[0038] S3, stacking, hot pressing, and cooling a plurality of prepregs to obtain a target product;
[0039] According to actual needs, the prepregs can be flexibly designed to be stacked. Prepregs with the same formula and physical properties can be stacked, or prepregs of multiple different specifications can be stacked and combined in a certain order to obtain a stacked composite layer; the stacked composite layer is then placed between two stainless steel plates covered with release films, and transferred to a press for staged heating, pressurization and heat preservation; the temperature is lowered to room temperature, and the fully hot-pressed composite layer is disassembled from the stainless steel plate to obtain a 2D structured, lightweight, high-frequency, wave-transparent composite material with low dielectric properties.
[0040] The curing agent includes one or more of active ester, styrene maleic anhydride resin, benzoxazine resin and bismaleimide resin. These curing agents with extremely low polarity are selected to reduce the dielectric loss of the composite material to below 0.01.
[0041] The dielectric loss of epoxy resin composites cured by traditional curing agents such as dicyandiamide and phenolic resin is basically above 0.012. The reaction mechanism of using amines and active esters to cure epoxy resin is compared. Figure 2 As shown, the curing reaction using these traditional curing agents is accompanied by the ring-opening reaction of the epoxy group to generate secondary alcohol hydroxyl groups, resulting in a large amount of polar hydroxyl groups in the cured product. The active ester contains two or more ester groups with higher activity, and there is no secondary alcohol hydroxyl group in the cured product after reacting with the epoxy resin, so it has lower dielectric loss and water absorption. In practical applications, styrene is a non-polar group in styrene-maleic anhydride copolymer, which has lower dielectric loss. Maleic anhydride, as a curing agent for epoxy resin, can avoid the generation of polar hydroxyl groups in the curing reaction process, increase the ratio of styrene groups in the copolymer, and further reduce dielectric loss.
[0042] If the dielectric loss of the composite material needs to be further reduced to below 0.008, special resins with lower polarity such as benzoxazine resin and bismaleimide resin are selected. Benzoxazine has good molecular structure design. By introducing dicyclopentadiene, the dielectric constant of benzoxazine resin can be reduced to 2.8, and the dielectric loss can reach 0.005. The dicyclopentadiene group also improves the brittleness of benzoxazine. Cyanate resins can also be used. There are many types of them, and different structures will have different properties. They are network polymers with highly symmetrical triazine ring structures generated after curing polymerization. They can have a stable dielectric constant of 2.7-3.0 and a dielectric loss of less than 0.007 in a wide frequency range of 1MHz-10GHz. At the same time, cyanate resins also have good adhesion, heat resistance and mechanical properties, and the Tg after curing is above 230℃. In practical applications, cyanate ester itself has certain brittleness and high water absorption, which can be overcome by modifying it through bismaleimide resin, such as bismaleimide triazine resin formed by copolymerization of bismaleimide and cyanate ester.
[0043] In addition to using low-grade curing agents to reduce the dielectric loss of composite materials, non-polar groups can also be introduced into epoxy resins to modify the epoxy resins. The use of modified epoxy resins can not only reduce dielectric loss, but also improve the water absorption, toughness, heat resistance, etc. of the target product.
[0044] Specifically, the epoxy resin includes one or more of bisphenol A epoxy resin, isocyanate-modified epoxy resin, dicyclopentadiene-modified epoxy resin and biphenyl-type epoxy resin. The use of low-polarity epoxy resin can achieve lower dielectric constant and dielectric loss. In practical applications, the use of isocyanate-modified epoxy resin can improve the toughness of the composite material.
[0045] The present invention adds high-performance hollow glass microspheres to a low-polarity epoxy resin composition, so that the obtained composite material has the characteristics of low density, low dielectric and high strength. Compared with the traditional epoxy glass fiber composite material filled with hollow glass microspheres, it has lower dielectric loss and the dielectric loss at 5GHz is less than 0.01, so it has higher high-frequency signal transmittance, which fully meets the demand for consumer electronic product casings and peripheral products in the 5G communication era.
[0046] Specifically, the mass fractions of each component in the resin glue are: 80-120 parts of epoxy resin, 20-100 parts of curing agent; 0.5-1.5 parts of accelerator; 0-150 parts of hollow glass microspheres. In actual production, each component of the resin glue (except the solvent) is calculated by weight of the non-volatile matter, and by using a solvent, the solid content of the resin glue is controlled to 50-75%. In practical applications, the amount of curing agent used is 20-100 parts, which can take into account the equivalent and dielectric properties of the groups involved in the curing reaction, while maximizing the overall dielectric properties, and avoiding excessive amounts that lead to a decrease in other overall properties, such as mechanical strength, interlayer bonding, etc.
[0047] Specifically, the accelerator includes one or more of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, N,N-dimethylaminopyridine and 2,4,6-tris(dimethylaminomethyl)phenol, which can reduce the temperature of the curing reaction and accelerate the curing reaction speed.
[0048] Specifically, the solvent includes one or more of acetone, butanone, xylene, propylene glycol methyl ether, ethylene glycol monomethyl ether and cyclohexanone to dissolve and disperse other components and adjust the viscosity to a suitable range for easy gluing.
[0049] Specifically, the hollow glass microspheres are high-performance borosilicate hollow glass microspheres, and the density of the high-performance borosilicate hollow glass microspheres is 0.2-0.6 g / cm 3, particle size D50 is 30-75 μm, particle size D90 is 60-120 μm. Further, the density of high performance borosilicate hollow glass microspheres is preferably 0.3-0.5 g / cm 3 , particle size D50 is 40-60μm, particle size D90 is 60-90μm. Compared with conventional hollow glass microspheres, high-performance borosilicate hollow glass microspheres have lower dielectric loss, and the dielectric constant and dielectric loss of the composite material can be further reduced by using high-performance borosilicate hollow glass microspheres.
[0050] Specifically, S1 also includes adding an auxiliary agent, which includes one or more of a pigment, a crosslinking auxiliary agent, an initiator, an antioxidant, and a UV absorber. The pigment may be a powder, including one or more of titanium dioxide, carbon black, solvent black, and aniline black, etc.; or it may be a completely ground color paste. The crosslinking auxiliary agent may be triallyl isocyanurate. In practical applications, when the formula uses a resin with more double bonds, a small amount of initiator needs to be added.
[0051] Specifically, in S3, an interlayer is stacked between two adjacent prepreg sheets, and the interlayer includes one of a plate, a metal sheet, a magnet, a prepreg and a fiber cloth to meet different actual needs.
[0052] Specifically, the specific steps of hot pressing in S3 are:
[0053] The composite layer is hot pressed in a step-by-step heating and pressurizing manner, with a hot pressing temperature of 120-220°C and a hot pressing pressure of 5-25kg / cm 2 ;
[0054] Then, the composite layer is heat-pressed at 170-190° C. for 30-120 minutes.
[0055] A light-weight high-frequency wave-transmitting composite material with low dielectric properties is prepared by the preparation method of the light-weight high-frequency wave-transmitting composite material with low dielectric properties.
[0056] Example 1
[0057] This embodiment provides a lightweight high-frequency wave-transmitting composite material with low dielectric properties, and the specific preparation steps are as follows:
[0058] S1, add 100 parts of bisphenol A epoxy resin with an epoxy equivalent weight of 450 g / eq, 64 parts of active ester, and 0.15 parts of N,N-dimethylaminopyridine to 80 parts of butanone and 25 parts of acetone, stir and disperse evenly, and then add 35 parts of a density of 0.38 g / cm 3 High-performance borosilicate hollow glass microspheres are added into the mixed solution and stirred evenly to obtain a resin glue solution;
[0059] S2, immerse 7628 glass fiber cloth into the resin glue solution, take it out after it is completely soaked, and bake it in a 175℃ oven for 5 minutes to obtain a semi-cured sheet, whose resin content RC value is 42.5% and resin fluidity RF is 5%;
[0060] S3, stack 4 prepregs of the same specifications to obtain a composite layer, transfer the composite layer to a hot press, heat press the temperature from 120°C to 185°C in stages, and heat press pressure from 5kg / cm 2 Stepwise pressurization up to 15kg / cm 2 , and then hot-pressed at 185°C for 90 min, cooled to room temperature, and disassembled to obtain the target product with a thickness of 1 mm.
[0061] Example 2
[0062] This embodiment provides a lightweight high-frequency wave-transmitting composite material with low dielectric properties, and the specific preparation steps are as follows:
[0063] S1, add 100 parts of dicyclopentadiene modified epoxy resin with an epoxy equivalent weight of 300 g / eq, 60 parts of styrene maleic anhydride resin, 6 parts of crosslinking aid, 0.1 parts of initiator, 0.1 parts of 2-ethyl-4-methylimidazole to 115 parts of butanone, stir and disperse evenly, then add 50 parts of a density of 0.38 g / cm 3 High-performance borosilicate hollow glass microspheres are added into the mixed solution and stirred evenly to obtain a resin glue solution;
[0064] S2. Immerse the 2116 glass fiber cloth in the resin glue solution, take it out after it is completely soaked, and bake it in a 175°C oven for 4 minutes to obtain a semi-cured sheet, whose resin content RC value is 42.5% and resin fluidity RF is 5%;
[0065] S3, stack three prepregs of the same specifications to obtain a composite layer, transfer the composite layer to a hot press, heat press the temperature from 120°C to 185°C in stages, and heat press pressure from 5kg / cm 2 Stepwise pressurization up to 12kg / cm 2 , and then hot-pressed at 185°C for 120 min, cooled to room temperature, and disassembled to obtain the target product with a thickness of 0.4 mm.
[0066] Example 3
[0067] This embodiment provides a lightweight high-frequency wave-transmitting composite material with low dielectric properties, and the specific preparation steps are as follows:
[0068] S1, add 100 parts of dicyclopentadiene modified epoxy resin with an epoxy equivalent weight of 300 g / eq, 60 parts of styrene maleic anhydride resin, 6 parts of crosslinking aid, 0.1 parts of initiator, 0.1 parts of 2-ethyl-4-methylimidazole to 100 parts of butanone, stir and disperse evenly, then add 25 parts of a density of 0.46 g / cm 3 High-performance borosilicate hollow glass microspheres are added into the mixed solution and stirred evenly to obtain a resin glue solution;
[0069] S2. Immerse the 2116 glass fiber cloth in the resin glue solution, take it out after it is completely soaked, and bake it in a 180°C oven for 4.5 minutes to obtain a semi-cured sheet, whose resin content RC value is 48% and resin fluidity RF is 7%;
[0070] S3, stack three prepregs of the same specifications to obtain a composite layer, transfer the composite layer to a hot press, heat press the temperature from 120°C to 185°C in stages, and heat press pressure from 5kg / cm 2 Stepwise pressurization up to 15kg / cm 2 , and then hot-pressed at 185°C for 120 min, cooled to room temperature, and disassembled to obtain the target product with a thickness of 0.4 mm.
[0071] Example 4
[0072] This embodiment provides a lightweight high-frequency wave-transmitting composite material with low dielectric properties, and the specific preparation steps are as follows:
[0073] S1, add 30 parts of bisphenol A epoxy resin with an epoxy equivalent of 450 g / eq, 30 parts of isocyanate modified epoxy resin with an epoxy equivalent of 300 g / eq, 25 parts of phenol biphenyl epoxy resin with an epoxy equivalent of 275 g / eq, 30 parts of styrene maleic anhydride resin, 20 parts of modified benzoxazine resin, 10 parts of modified bismaleimide resin, 8 parts of crosslinking aid, 0.1 parts of initiator, 0.1 parts of 2-ethyl-4-methylimidazole to 135 parts of butanone, stir and disperse evenly, then add 65 parts of a density of 0.38 g / cm 3 High-performance borosilicate hollow glass microspheres are added into the mixed solution and stirred evenly to obtain a resin glue solution;
[0074] S2, immerse the 2116 glass fiber cloth into the resin glue, take it out after it is completely soaked, and bake it in a 180℃ oven for 4.5 minutes to obtain a semi-cured sheet, whose resin content RC value is 47.5% and resin fluidity RF is 5%;
[0075] S3, stack three prepregs of the same specifications to obtain a composite layer, transfer the composite layer to a hot press, heat press temperature is increased from 120 ° C to 190 ° C in stages, and the hot press pressure is increased from 5 kg / cm 2 Stepwise pressurization up to 10kg / cm 2 , and then hot-pressed at 190°C for 120 min, cooled to room temperature, and disassembled to obtain the target product with a thickness of 0.5 mm.
[0076] Comparative Example 1
[0077] This comparative example provides a composite material, and the specific preparation steps are as follows:
[0078] S1, adding 100 parts of bisphenol A epoxy resin with an epoxy equivalent weight of 450 g / eq to 35 parts of acetone, stirring and dispersing the mixture evenly to obtain a first solution;
[0079] 2.2 parts of dicyandiamide and 0.06 parts of 2-methylimidazole are added to 30 parts of ethylene glycol monomethyl ether, and dissolved and dispersed uniformly to obtain a second solution;
[0080] Add the second solution to the first solution and stir evenly. Then add 22 parts of a density of 0.38 g / cm 3 High-performance borosilicate hollow glass microspheres are added into the mixed solution and stirred evenly to obtain a resin glue solution;
[0081] S2, immerse 7628 glass fiber cloth into the resin glue, take it out after it is completely soaked, and bake it in a 165℃ oven for 4 minutes to obtain a semi-cured sheet, whose resin content RC value is 42.5% and resin fluidity RF is 5%;
[0082] S3, stack 4 prepregs of the same specifications to obtain a composite layer, transfer the composite layer to a hot press, heat press the temperature from 120°C to 170°C in stages, and heat press pressure from 5kg / cm 2 Stepwise pressurization up to 15kg / cm 2 , and then hot-pressed at 170°C for 90 min, cooled to room temperature, and disassembled to obtain the target product with a thickness of 1 mm.
[0083] Comparative Example 2
[0084] This comparative example provides a composite material, and the specific preparation steps are as follows:
[0085] S1, adding 80 parts of bisphenol A epoxy resin with an epoxy equivalent of 450 g / eq and 20 parts of bisphenol A epoxy resin with an epoxy equivalent of 185 g / eq to 35 parts of acetone, stirring and dispersing them uniformly to obtain a first solution;
[0086] Add 3 parts of dicyandiamide and 0.07 parts of 2-methylimidazole to 45 parts of ethylene glycol monomethyl ether, dissolve and disperse them uniformly, and obtain a second solution;
[0087] Add the second solution to the first solution and stir evenly. Then add 42 parts of a density of 0.38 g / cm 3 High-performance borosilicate hollow glass microspheres are added into the mixed solution and stirred evenly to obtain a resin glue solution;
[0088] S2. Immerse the 2116 glass fiber cloth in the resin glue solution, take it out after it is completely soaked, and bake it in a 165°C oven for 3.5 minutes to obtain a semi-cured sheet, whose resin content RC value is 47.5% and resin fluidity RF is 5%;
[0089] S3, stack three prepregs of the same specifications to obtain a composite layer, transfer the composite layer to a hot press, heat press temperature is increased from 120 ° C to 170 ° C in stages, and the hot press pressure is increased from 5kg / cm 2 Stepwise pressurization up to 15kg / cm 2 , and then hot-pressed at 170°C for 90 min, cooled to room temperature, and disassembled to obtain the target product with a thickness of 0.5 mm.
[0090] The mass fractions of the materials used in the above embodiments and comparative examples are all their effective ingredients. When preparing the resin glue, when adding a solid material that is difficult to dissolve, it can be dissolved in a solvent first and then added to the resin glue to avoid affecting the preparation of the target product due to insufficient dissolution.
[0091] The materials used in the above embodiments and comparative examples are as follows:
[0092] Resin: The bisphenol A epoxy resin is Nan Ya NPES901 or NPEL128, the manufacturer of isocyanate modified epoxy resin is Tongyu New Materials (Guangdong) Co., Ltd., model TER296K75, the manufacturer of dicyclopentadiene modified epoxy resin is Chengdu Keyi Polymer Technology Co., Ltd., model CE1000, the manufacturer of biphenyl type epoxy resin is Shandong Shengquan Chemical Co., Ltd., model SQXN-323, the manufacturers of modified benzoxazine resin and modified bismaleimide resin are both Tongyu New Materials (Guangdong) Co., Ltd., the model of modified benzoxazine resin is TBN8730K70, and the model of modified bismaleimide resin is TBM7200.
[0093] Curing agent: The manufacturer of active ester is LTY19015 model of Tongyu New Materials (Guangdong) Co., Ltd. or DFE617L model of Sichuan Dongcai Technology Group Co., Ltd., and the manufacturer of styrene maleic anhydride is EF-30 model produced by Crayville (Guangzhou) Chemical Co., Ltd. or TMH8003 model produced by Tongyu New Materials (Guangdong) Co., Ltd.
[0094] Accelerator: 2-ethyl-4-methylimidazole is 2E4Mz from Siguo Chemical.
[0095] Hollow glass microspheres: H38 or H46 from Zhongke Yali.
[0096] The relevant performance tests were carried out on the embodiments and comparative examples, and the results are as follows:
[0097] Table 1
[0098] Table 1 records the density, bending strength, dielectric constant and dielectric loss at 5GHz of each embodiment and comparative example. In each embodiment using a low-polarity curing agent, the dielectric loss at 5GHz is less than 0.01, while in each comparative example not using a low-polarity curing agent, the dielectric loss at 5GHz is higher than 0.01. Comparing Example 4 with Comparative Example 2, it can be seen that: under the same density, the dielectric loss of Example 4 is lower. In addition, the thickness of Example 1 and Comparative Example 1 is 1mm, which is suitable for larger 5G consumer electronic products, such as tablet computers and their housings, and the thickness of other embodiments and comparative examples is 0.4-0.5mm, which is suitable for small-sized 5G consumer electronic products, such as the housing of the back cover of a 5G mobile phone. The composite material prepared by the present invention has low density, low dielectric and high strength properties, while having lower dielectric loss than the traditional epoxy glass fiber composite material filled with hollow glass microspheres.
[0099] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A lightweight high-frequency wave-transmitting composite material with low dielectric properties, characterized in that: The following steps are involved: S1. Add epoxy resin, curing agent and accelerator to the solvent, stir and evenly dissolve, then add hollow glass microspheres, stir and evenly disperse to obtain resin glue; S2, immersing the glass fiber cloth into the resin glue solution, taking it out after it is completely soaked, and baking it to obtain a prepreg; S3, stacking a plurality of the prepregs to obtain a composite layer, hot pressing and cooling the composite layer to obtain a target product; Among them, the curing agent includes one or more of active ester, styrene maleic anhydride resin, benzoxazine resin and bismaleimide resin, and the epoxy resin includes one or more of bisphenol A type epoxy resin, isocyanate modified epoxy resin, dicyclopentadiene modified epoxy resin and biphenyl type epoxy resin.
2. The method for preparing a lightweight high-frequency wave-transmitting composite material with low dielectric properties according to claim 1, characterized in that: The mass fractions of each component in the resin glue are: Epoxy resin 80-120 parts; Curing agent 20-100 parts; Accelerator 0.05-0.5 parts; Hollow glass microspheres 20-80 parts.
3. The method for preparing a lightweight high-frequency wave-transmitting composite material with low dielectric properties according to claim 1, characterized in that: The accelerator includes one or more of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, N,N-dimethylaminopyridine and 2,4,6-tris(dimethylaminomethyl)phenol.
4. The method for preparing a lightweight high-frequency wave-transmitting composite material with low dielectric properties according to claim 1, characterized in that: The solvent includes one or more of acetone, butanone, xylene, propylene glycol methyl ether, ethylene glycol monomethyl ether and cyclohexanone.
5. The method for preparing a lightweight high-frequency wave-transmitting composite material with low dielectric properties according to claim 1, characterized in that: The hollow glass microspheres are high-performance borosilicate hollow glass microspheres, and the density of the high-performance borosilicate hollow glass microspheres is 0.2-0.6 g / cm 3 , particle size D50 is 30-75μm, and particle size D90 is 60-120μm.
6. A lightweight high-frequency wave-transmitting composite material with low dielectric properties and a preparation method thereof according to claim 1, characterized in that: The step S1 further includes adding an auxiliary agent, wherein the auxiliary agent includes one or more of a pigment, a cross-linking auxiliary agent, an initiator, an antioxidant and an ultraviolet absorber.
7. The method for preparing a lightweight high-frequency wave-transmitting composite material with low dielectric properties according to claim 1, characterized in that: In S3, an interlayer is stacked between the prepregs, and the interlayer includes one of a plate, a metal sheet, a magnet, a prepreg and a fiber cloth.
8. The method for preparing a lightweight high-frequency wave-transmitting composite material with low dielectric properties according to claim 1, characterized in that: The specific steps of hot pressing in S3 are: The composite layer is hot pressed in a stepwise manner with a temperature of 120-220°C and a pressure of 5-25 kg / cm 2 ; Then, the composite layer is heat-pressed at 170-190° C. for 30-120 minutes.
9. A lightweight high-frequency wave-transmitting composite material with low dielectric properties, characterized in that: The composite material is prepared according to the method for preparing a lightweight high-frequency wave-transmitting composite material with low dielectric properties according to any one of claims 1-8.
Citation Information
Patent Citations
High-Tg lightweight composite material and preparation method thereof
CN109825033A
Metamaterial substrate and preparation method thereof
CN102477210A
Benzoxazine resin composition for millimeter-wave radar antenna housing and preparing method of benzoxazine resin composition
CN104945901A
Prepreg, preparation method of prepreg and composite material
CN106317770A
Thermosetting resin ultralow-density laminated material and preparation method thereof
CN106739294A
Cited By
Cryo- and fire protection system for metal structures of the oil and gas sector
RU2854297C1